Amorphous silica-magnesia composite and method for producing the same
Patent Information
- Application Number
- JP2023125520
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0010】 本発明は、シリカとマグネシアとが一体化した非晶質シリカマグネシア複合体であって、特定量のマグネシウムを含むものである。この構成により、本発明の非晶質シリカマグネシア複合体は従来品と比較して脂肪酸吸着能が著しく向上している。
Smart Images

Figure 2025021655000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an amorphous silica-magnesia composite and a method for producing the same, and in particular to an amorphous silica-magnesia composite that is suitably used for removing free fatty acids contained in edible oils, and a method for producing the same. [Background technology]
[0002] Silica-magnesia composites containing silica and magnesia are used in many fields due to their high adsorption capacity. For example, Patent Document 1 discloses a silica-magnesia composite as a chromatography packing material useful for separating basic substances. Patent Document 2 discloses a silica-magnesia composite as a treatment agent for wastewater containing phosphoric acid.
[0003] From the viewpoint of safety, the silica-magnesia complex is also used as an adsorbent in the food industry. For example, the silica-magnesia complex is used as a caffeine adsorbent (Patent Document 3) or a trigonelline adsorbent (Patent Document 4).
[0004] Here, edible oil is a natural oil extracted from animals and plants, and contains fatty acid glycerides as a main component. Since such edible oil contains free fatty acids and pigments, it is necessary to remove these impurities using a specified refining agent before using it for food. In addition, used edible oil used for deep-frying and the like also contains a large amount of free fatty acids generated by thermal decomposition of glycerides and also contains a large amount of pigment components. For this reason, when used edible oil is regenerated and reused, the above-mentioned refining agent is used to remove the free fatty acids and pigments (decolorization).
[0005] As the edible oil refining agent, an edible oil refining agent made of silica-magnesia composite particles is known. For example, Patent Documents 5 to 8 disclose edible oil refining agents made of silica-magnesia composite particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 6-27097 [Patent Document 2] Patent Publication No. 2015-178064 [Patent Document 3] Patent Publication No. 2018-94512 [Patent Document 4] Patent Publication No. 2020-179334 [Patent Document 5] Patent Publication No. 2005-6510 [Patent Document 6] Patent Publication No. 2005-8675 [Patent Document 7] Patent Publication No. 2019-81157 [Patent Document 8] Special table number 2022-528344 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an amorphous silica-magnesia composite having excellent adsorption ability for fatty acids. Another object of the present invention is to provide an amorphous silica-magnesia composite having at least one of excellent anion adsorption ability, cation adsorption ability, and fatty acid adsorption ability. [Means for solving the problem]
[0008] As a result of furthering research into silica-magnesia composites in which silica and magnesia are integrated, the inventors discovered that the adsorption capacity for fatty acids can be improved by adjusting the magnesium content contained in the amorphous silica-magnesia composite, and thus completed the present invention.
[0009] That is, the present invention and its various aspects are as follows. However, the present invention is not limited to the following. [1] An amorphous silica-magnesia composite comprising silica and magnesia, The content (mass%) of magnesia component in terms of MgO is 0.5 to 40%. Amorphous silica-magnesia composite. [2] The amorphous silica-magnesia composite according to [1], wherein the mass ratio R represented by the following formula is 1.0 to 50: R=Sm / Mm In the formula, Sm is SiO 2 The silica content (mass%) is calculated as Mm is as defined in [1]. [3] The Orange II adsorption capacity per gram of amorphous silica-magnesia composite is 0.4 mmol / g or more; and The Orange II adsorption capacity per gram of magnesia component (calculated as MgO) is 3.0 mmol / g or more. [1] An amorphous silica-magnesia composite according to the present invention. [4] A method for making an amorphous silica-magnesia composite, comprising the steps of mixing a silicate solution and a magnesium sulfate solution. [5] The method according to [4], wherein the step of mixing the silicate solution and the magnesium sulfate solution is carried out so that the pH of the resulting mixed solution is in the range of 1 to 3. [6] The method according to [5], further comprising a step of performing an alkali treatment with aqueous ammonia after the step of mixing the silicate solution and the magnesium sulfate solution is performed so that the pH of the resulting mixed solution falls within the range of 1 to 3. [7] The method according to [4], wherein the step of mixing the silicate solution and the magnesium sulfate solution is carried out so that the pH of the resulting mixture is in the range of 9 to 11. Effect of the Invention
[0010] The present invention is an amorphous silica-magnesia composite in which silica and magnesia are integrated, and contains a specific amount of magnesium. Due to this constitution, the amorphous silica-magnesia composite of the present invention has a significantly improved fatty acid adsorption ability compared to conventional products.
[0011] In addition, since the amorphous silica-magnesia composite of the present invention contains silica in a state of being integrated with magnesia, even if soap is produced by absorbing fatty acid, the soap will not be liberated from the amorphous silica-magnesia composite, and therefore, when used for refining edible oil, soap can be prevented from being dispersed in the edible oil. [Brief description of the drawings]
[0012] [Figure 1] 1 shows X-ray diffraction of Examples 2, 3, and 4 of the present invention. [Diagram 2] 1 shows X-ray diffraction of Comparative Examples 2 and 3 of the present invention, and Mg(OH)2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <Amorphous silica-magnesia composite> The amorphous silica-magnesia composite of the present invention is a combination of silicon dioxide (referred to as "silica" in this specification) and magnesium oxide (referred to as "magnesia" in this specification). This composite is not formed by a chemical bond involving the recombination or exchange of atoms between silica and magnesia, but rather means a state in which the fine particles of each are in close contact with each other to a level where they are not physically separated, and is completely different from a simple mixture.
[0014] The amorphous silica-magnesia composite of the present invention is believed to have a structure in which silica particles enclose magnesia particles. It is believed that the silica-magnesia composite has such a structure that it has improved adsorption ability for fatty acids.
[0015] The fact that the silica-magnesia composite has an amorphous structure can be confirmed, for example, by X-ray diffraction measurement. If the silica-magnesia composite is amorphous, it will not show any specific peak in X-ray diffraction.
[0016] <Magnesium content> The amorphous silica-magnesia composite of the present invention contains a magnesia component as described above. The magnesia component contained in the amorphous silica-magnesia composite of the present invention is expressed in terms of MgO, and the content (mass %) of the magnesia component in terms of MgO, Mm, is 0.5 to 30%. Mm is preferably 1 to 20%, more preferably 2 to 15%. It is believed that when Mm is 0.5% or more, the adsorption ability for fatty acids is improved.
[0017] The amorphous silica-magnesia composite of the present invention contains a silica component and a magnesia component, and the mass ratio R of the silica component to the magnesia component is represented by the following formula. R=Sm / Mm Here, Sm is SiO 2 Mm is the content (mass %) of the magnesia component converted into MgO, as described above. In one embodiment of the present invention, the mass ratio R is 1.0-50, preferably 1.5-45, and more preferably 5.0-43. When the mass ratio R is 50 or less, the required amount of magnesia component is secured relative to the silica component, so that the desired deoxidizing performance can be obtained. Also, when the mass ratio R is 1.0 or more, the content of the silica component relative to the magnesia component is high, so that the function as a silica binder can be obtained. When the mass ratio R is within the above range, when soap is generated by reaction of magnesia with fatty acid, the separation of soap can be prevented. Also, when used as a refining agent for edible oil, the decolorizing performance can be improved. That is, when the mass ratio R is within the above range, the amorphous silica-magnesia composite of the present invention can be suitably used as an adsorbent for edible oil.
[0018] In one embodiment of the present invention, the specific surface area of the amorphous silica-magnesia composite is 200 to 700 m 2 The specific surface area is preferably 300 to 670 m 2 / g, more preferably 530 to 650 m 2 / g. The specific surface area is 200m 2 / g or more, browning / coloring components, volatile base components, and / or impurities such as free fatty acids and iron can be stably adsorbed and removed.
[0019] The specific surface area of the amorphous silica-magnesia composite can be reduced by hydrothermal treatment during the production of the amorphous silica-magnesia composite. For example, the hydrothermal treatment method includes heating the amorphous silica-magnesia composite in water or in an autoclave. By hydrothermal treatment, the silica primary particles of the amorphous silica-magnesia composite melt together and become larger, resulting in a decrease in the specific surface area and an increase in the pore volume.
[0020] In one embodiment of the present invention, the pore volume of the amorphous silica-magnesia composite is 0.3 to 2.0 cm 3 The pore volume is preferably 0.4 to 2.0 cm3 / g. 3 / g, more preferably 0.5 to 2.0 cm 3 / g. The pore volume is 0.3 cm 3 / g or more, the decolorization performance of waste oil can be improved.
[0021] As described above, the pore volume of the amorphous silica-magnesia composite can be increased by the hydrothermal treatment carried out during the production of the amorphous silica-magnesia composite.
[0022] <Anion adsorption capacity> In one embodiment of the present invention, the amorphous silica-magnesia composite exhibits excellent anion adsorption ability. Here, since orange II is an anionic pigment, the anion adsorption ability can be expressed as the amount of orange II that can be adsorbed per 1g of the amorphous silica-magnesia composite, and the amount of orange II that can be adsorbed per 1g of the magnesia component content in terms of MgO contained in the amorphous silica-magnesia composite. That is, the larger the amount of orange II that can be adsorbed, the higher the deacidification performance, and for example, the more effectively the free fatty acid in edible oil can be adsorbed. This is considered to be because the carboxyl group contained in the fatty acid generates anion under basic conditions, and the amorphous silica-magnesia composite of the present invention adsorbs the anion.
[0023] In one embodiment of the present invention, the amorphous silica-magnesia complex has an Orange II adsorption capacity of 0.4 mmol / g or more per 1 g. The amorphous silica-magnesia complex can function suitably as an edible oil refining agent by having an Orange II adsorption capacity of 0.4 mmol / g or more per 1 g.
[0024] Furthermore, in one embodiment of the present invention, the amorphous silica-magnesia composite has an Orange II adsorption capacity of 3.0mmol / g or more per 1g of the magnesia component content calculated as MgO. The higher the Orange II adsorption capacity per 1g of the magnesia component content calculated as MgO, the more suitable it can function as an edible oil refining agent. Incidentally, the anion adsorption capacity per 1g of the magnesia component content calculated as MgO is generally less than 2.5mmol / g.
[0025] <Cation adsorption capacity> In one embodiment of the present invention, the amorphous silica-magnesia composite has excellent cation adsorption ability, and therefore exhibits high adsorption and removal ability of browning and coloring components. The cation adsorption ability can be evaluated, for example, by the amount of adsorption of methylene blue, which is a basic dye having an amino group like melanoidin and exhibits a high chroma blue color, making it easy to determine the titration end point and the like. In addition, the cation adsorption ability can also be evaluated by measuring the absorbance of the oil after a predetermined decolorization treatment with an amorphous silica-magnesia composite, using frying oil after repeated use as a test oil, and calculating the reduction rate of coloring. The above evaluation methods have almost the same tendency.
[0026] The cation adsorption capacity of the amorphous silica-magnesia composite is 0.3 to 0.7 mmol / g when measured by the amount of methylene blue adsorbed. The adsorption capacity is preferably 0.35 to 0.65 mmol / g. When the cation adsorption capacity is 0.3 mmol / g or more, the composite can function suitably as an edible oil refining agent.
[0027] <Fatty acid adsorption capacity (deacidification of waste oil)> The amorphous silica-magnesia composite of the present invention has an excellent deoxidizing ability, which can be expressed as a deoxidizing rate calculated by the following formula: Deoxidation rate (%) = (acid value of test oil - acid value of treated oil) / (acid value of test oil) x 100 The deoxidizing ability of the amorphous silica-magnesia composite of the present invention is 16% or more, preferably 19% or more, and more preferably 20% or more. As described above, the amorphous silica-magnesia composite of the present invention has a structure in which silica particles enclose magnesia particles, and since the dispersibility of magnesium, which is an active ingredient, is high, it is believed to have excellent deoxidizing ability.
[0028] <Production of amorphous silica-magnesia composite> The present invention also provides a novel method for producing an amorphous silica-magnesia composite. The method for producing an amorphous silica-magnesia composite of the present invention includes a step of mixing a silicate solution and a magnesium sulfate solution. That is, by mixing a silicate solution and a magnesium sulfate solution, a silica hydrogel is obtained in a sol state, and the silica hydrogel is appropriately treated to obtain an amorphous silica-magnesia composite. According to this production method, compared to conventional production methods in which raw materials are mixed between solids or between solid and liquid, it is expected that magnesium will be highly dispersed in the silica matrix because the raw materials are mixed between solutions. In addition, the effective ingredient magnesium is highly dispersed in the silica matrix with a large specific surface area, and thus the adsorption ability, which is the target property, can be improved.
[0029] In the above-mentioned manufacturing method, sodium silicate and sulfuric acid are mixed so that the solid content concentration is 3% or more, and a gel is generated through a sol state, which is a so-called sol-gel reaction. The time it takes for the sol to change into a gel (gelation time) is greatly affected by the pH. The gelation time is maximum at pH 2, which is the isoelectric point of silica, and is minimum at pH 7 to 8. In the alkaline region, the gelation time increases as the pH increases, and eventually gelation ceases. In the manufacturing method of the present invention, the amorphous silica-magnesia composite can be synthesized in an acidic or alkaline region in order to maintain a moderate sol state from the viewpoint of performing an industrially uniform reaction.
[0030] In one aspect of the present invention, the step of mixing the silicate solution and the magnesium sulfate solution is preferably carried out such that the pH of the resulting mixture is in the range of 1 to 3. In this case, the silicate solution may be an acidic sol of silicic acid (such as sodium silicate). Specifically, when producing amorphous silica-magnesia, a sol can be prepared by mixing sodium silicate, sulfuric acid, and magnesium salt solutions so that the pH is in the range of 1 to 3. When producing amorphous silica-magnesia in an acidic range, the sol naturally gels after the mixing, and magnesium remains in the form of ions. An amorphous silica-magnesia composite can then be obtained by performing an alkali treatment. The amorphous silica-magnesia composite can then be washed with water, dried, pulverized, classified, and fired as necessary.
[0031] The alkaline treatment is a step of precipitating magnesium hydroxide by adjusting the pH of the mixture obtained to a range of 9 to 11 using an alkaline aqueous solution. The alkaline aqueous solution is not particularly limited, and various aqueous solutions exhibiting alkaline properties can be used. Ammonia water is preferred as the alkaline aqueous solution, since silica is not dissolved therein and magnesium can be stably immobilized.
[0032] In one embodiment of the present invention, the step of mixing the silicate solution and the magnesium sulfate solution is preferably carried out so that the pH of the resulting mixture is in the range of 9 to 11. In this case, the silicate solution may be an alkali sol of silicic acid. Specifically, when producing an amorphous silica-magnesia composite, an alkali sol of silicic acid is mixed with a sulfate solution of magnesium salt so that the pH is in the range of 9 to 11 to carry out a sol-gel reaction. In the alkaline range, magnesium hydroxide is precipitated first in the matrix of the silica sol, and the silica gels over a certain period of time to obtain a silica-magnesia composite. Therefore, a silica-magnesia composite can be obtained without performing an alkali treatment in the acid range. Thereafter, the obtained silica-magnesia composite is washed with water, dried, pulverized, classified, and fired as necessary to obtain the amorphous silica-magnesia composite of the present invention.
[0033] The above-mentioned washing with water, drying, pulverization, classification and firing can be carried out by a commonly used method.
[0034] For example, the drying method may be to remove water by evaporation using a flash dryer or a spray dryer. After dehydration to a certain extent by means of filtration or centrifugation, drying may be performed using a box dryer, band dryer, fluidized bed dryer, etc. Drying may be performed at a temperature in the range of 110 to 350°C.
[0035] For example, the pulverization can be carried out using an impact pulverizer such as an atomizer, a dry ball mill, a roller mill, a jet mill, or the like. The classification method can be gravity classification, centrifugal classification, inertial classification, or the like, using a conventional dry classifier.
[0036] As already mentioned, the amorphous silica-magnesia composite of the present invention is composed of silica-magnesia composite particles in which silica and magnesia components approved as food additives are integrated, and has excellent fatty acid adsorption performance, so it can be effectively applied to food purification applications. For example, it can be effectively used to regenerate frying oil that has deteriorated due to repeated use and contains a lot of free fatty acids and pigment components, remove impurities from raw materials and broths of concentrated seasoning liquids such as fish and shellfish extracts and livestock meat extracts that also contain a lot of free fatty acids and pigment components, suppress browning reactions (Maillard reactions) during heating and concentration, and prevent deterioration of flavor and nutritional value. It can also be effectively used to purify a wide range of useful liquids other than food by adsorbing and removing impurities. EXAMPLES
[0037] The excellent effects of the present invention will be explained by the following experimental examples.
[0038] (1) Orange II adsorption amount In the present embodiment, the Orange II adsorption capacity is defined as the number of mmoles of Orange II that 1 g of a sample can adsorb from an aqueous solution of Orange II with a concentration of 10 mmol / L, and was measured and calculated by the following method. First, Orange II (special grade reagent, manufactured by Wako Pure Chemical Industries, Ltd.) was dissolved in water to obtain an Orange II aqueous solution with a concentration of 10 mmol / L. 20 ml of this 10 mmol / L Orange II aqueous solution was weighed into a 50 ml centrifuge tube, 0.20 g of adsorbent was added, and the solution was shaken for 7.5 hours using a shaker (SA300 manufactured by Yamato Scientific Co., Ltd., shaking speed 5). After shaking, the solution was left to stand for 12 hours or more. Next, 1.0 mL of the supernatant of the solution treated at a centrifugal acceleration of 3000 rpm for 15 minutes using a centrifuge (5200 manufactured by Kubota Co., Ltd.) was collected, and the absorbance of the 484 nm wavelength light of the solution diluted 200 times with ion-exchanged water was measured using a spectrophotometer (V-630 manufactured by JASCO Corporation). The remaining amount of Orange II in the sample solution was calculated using a calibration curve showing the relationship between the Orange II content in the Orange II aqueous solution and the absorbance of the 484 nm wavelength light. This value was subtracted from the amount of Orange II added to the sample to obtain the amount of Orange II adsorbed.
[0039] (2) Methylene blue adsorption capacity In the present example, the methylene blue adsorption capacity was defined as the number of mmoles of Orange II that 1 g of a sample could adsorb from an aqueous methylene blue solution with a concentration of 6.25 mmol / L, and was measured and calculated by the following method. First, methylene blue trihydrate (special grade reagent, manufactured by Wako Pure Chemical Industries, Ltd.) was dissolved in water to obtain a methylene blue aqueous solution with a concentration of 6.25 mmol / L. 20 ml of this 6.25 mmol / L methylene blue aqueous solution was weighed into a 50 ml centrifuge tube, 0.10 g of adsorbent was added, and the solution was shaken for 7.5 hours using a shaker (SA300 manufactured by Yamato Scientific Co., Ltd., shaking speed 5). After shaking, the solution was left to stand for 12 hours or more. Next, 1.0 mL of the supernatant was taken from the solution that had been treated for 15 minutes at a centrifugal acceleration of 3000 rpm using a centrifuge (5200 manufactured by Kubota Co., Ltd.), and the absorbance of the 667 nm wavelength light of the solution diluted 200 times with ion-exchanged water was measured using a spectrophotometer (V-630 manufactured by JASCO Corporation). The amount of methylene blue remaining in the sample solution was calculated using a calibration curve showing the relationship between the methylene blue content in the methylene blue solution and the absorbance of 667 nm wavelength light. This value was subtracted from the amount of methylene blue added to the sample to determine the amount of methylene blue adsorbed.
[0040] (3) Free fatty acid adsorption test In the present embodiment, the free fatty acid adsorption test was carried out using a testing machine shown in the figure on page 570 of Clay Handbook, Third Edition, edited by the Clay Science Society of Japan (Gihodo Publishing). In the test machine, large hard glass test tubes (volume 230 ml) were set in an oil bath. A corrugated stirring rod with a rounded bottom was placed in each test tube, and the bottom end was adjusted with a rubber tube so that it was always in contact with the bottom of the test tube. The stirring rods were rotated by a child gear separated from the central parent gear, so their rotation speeds were kept exactly the same. Under the central parent gear was a stirring blade that stirred the oil bath, which kept the temperature inside the oil bath uniform. 50 g of used oil (transmittance 35.0-46.0%, acid value 2.10-2.22) was collected in each test tube, and 1 g of each adsorbent sample (2 mass % of the oil) was added. Each test tube was set in the above-mentioned test machine maintained at 110°C, and after stirring for 20 minutes, it was removed from the test machine and the mixed slurry of regenerated oil and adsorbent was filtered to obtain each regenerated oil. The acid value of each recycled oil was measured in accordance with the standard method for the analysis of fats, oils and oils 2.3.1-2013 established by the Japan Oil Chemists' Society. The difference from the acid value of the used oil was taken as the acid value reduction value (mgKOH / g), and the deoxidation rate was calculated as the free fatty acid adsorption capacity using the following formula. Deacidification rate (%) = (acid value of used oil - acid value of reclaimed oil) / (acid value of used oil) x 100 The larger this value, the greater the amount of free fatty acid adsorbed, indicating that the free fatty acid is being removed more effectively.
[0041] (4) BET specific surface area by nitrogen adsorption method Measurements were performed by nitrogen adsorption using a Micromeritics TriStar II 3020. The pore volume was calculated by integrating the pore volume with a pore diameter of 2.0 nm to 50 nm in the pore distribution calculated by the BJH method from the nitrogen adsorption isotherm on the desorption branch side. The specific surface area was analyzed by the BET method from the nitrogen adsorption isotherm on the adsorption branch side at a specific pressure of 0.05 to 0.20.
[0042] Example 1 Sodium silicate (SiO 2 22.5% by weight, Na 2O 7.2 wt%, SG 1.295 / 15°C) and 45 wt% sulfuric acid aqueous solution (SG 1.343 / 25°C) were mixed in a volume ratio (sodium silicate:sulfuric acid aqueous solution) of 15:4 to obtain an acidic silica sol. 2200 g of the acidic silica sol and 35.2 g of magnesium sulfate (anhydrous) were added to 138 g of water and mixed to produce a silica magnesium sol. This silica magnesia sol was left to stand and gelled, then treated with ammonia water and washed with tap water. After washing, the product obtained was dried and pulverized at 150°C to obtain a powdered amorphous silica magnesia composite.
[0043] Example 2 An amorphous silica-magnesia composite was obtained in the same manner as in Example 1, except that 1100 g of acidic silica sol, 23.7 g of magnesium sulfate (anhydrous) and 93 g of water were mixed.
[0044] Example 3 An amorphous silica-magnesia composite was obtained in the same manner as in Example 1, except that 950 g of acidic silica sol, 54.5 g of magnesium sulfate (anhydrous) and 214 g of water were mixed.
[0045] Example 4 An amorphous silica-magnesia composite was obtained in the same manner as in Example 1, except that 800 g of acidic silica sol, 78.7 g of magnesium sulfate (anhydrous) and 309 g of water were mixed.
[0046] Example 5 The raw material is sodium silicate (SiO 2 14.5% by weight, Na 2A magnesium sulfate aqueous solution was used in which 45.5 g of magnesium hydroxide was dissolved per 1000 g of a 16 wt% sulfuric acid aqueous solution (SG 1.11 / 20°C) and 3.49 L / min of the sodium silicate and 1.39 L / min of the magnesium sulfate aqueous solution were mixed using a two-fluid nozzle with a discharge port of 4 mmΦ, and the discharge port was directed diagonally upward at about 80° and released into the air, and the water in a PP receiving tank was allowed to fall, and silica-magnesia hydrogel was prepared by the sol-gel reaction of silica, followed by washing with tap water. After washing, the product obtained at 150°C was dried and pulverized to obtain a powdered amorphous silica-magnesia composite.
[0047] Comparative Example 1 The silica-magnesia preparation Mizuka Life F-2G manufactured by Mizusawa Chemical Industry Co., Ltd. was used.
[0048] Comparative Example 2 2.18 g of magnesium hydroxide was dispersed in 600 mL of water to obtain a magnesium hydroxide slurry. Hydrous silicon dioxide (Mizukasorb C-1, manufactured by Mizusawa Chemical Industry Co., Ltd.) was added to the magnesium hydroxide slurry to prepare a slurry. The slurry was stirred at 90°C for 4 hours. After stirring, the slurry was deliquored and dried to obtain a white powder.
[0049] Comparative Example 3 A white powder was obtained in the same manner as in Comparative Example 2, except that the stirring was carried out at room temperature.
[0050] Using an X-ray diffraction measurement device (Rigaku Corporation, product name: Ultima IV), X-ray diffraction measurements were performed on the powders obtained in Examples 2, 3, and 4, and Comparative Examples 2 and 3. The results of the X-ray diffraction measurements for Examples 2, 3, and 4 are shown in Figure 1. In addition, for Comparative Examples 2, 3, and Mg(OH) 2 The results of the X-ray diffraction measurement are shown in FIG. 2. In the X-ray diffraction of Comparative Examples 2 and 3 shown in FIG. 2, Mg(OH) 2 In contrast, in the X-ray diffraction of Examples 3, 4, and 5 shown in FIG. 1, peaks derived from Mg(OH) 2No peaks due to the above were observed, confirming that the silica-magnesia composite of the example is amorphous.
[0051] The measurement results of the examples and comparative examples are shown in Table 1. [Table 1] [Industrial Applicability]
[0052] The amorphous silica-magnesia composite of the present invention has excellent adsorption ability for fatty acids. In addition, the amorphous silica-magnesia composite of the present invention has at least one of excellent anion adsorption ability, cation adsorption ability, and fatty acid adsorption ability. Furthermore, as already mentioned, since it contains silica and magnesia components approved as food additives and has decolorization performance, it can be effectively applied to food purification applications. In addition, since it can be effectively used for purification by adsorption and removal of impurities from widely useful liquids other than food, it can be used in many fields where wastewater treatment is required.
Claims
1. An amorphous silica-magnesia composite comprising silica and magnesia, The content (mass%) Mm of the magnesia component calculated as MgO is 0.5 to 40%. Amorphous silica-magnesia composite.
2. The amorphous silica-magnesia composite according to claim 1, wherein the mass ratio R represented by the following formula is 1.0 to 50: R = Sm / Mm In the formula, Sm is SiO 2 is the content (mass%) of the silica component converted into Mm is as defined in claim 1.
3. The Orange II adsorption capacity per 1 g of the amorphous silica-magnesia composite is 0.4 mmol / g or more; and The Orange II adsorption capacity per 1 g of magnesia component calculated as MgO is 3.0 mmol / g or more.
2. The amorphous silica-magnesia composite of claim 1.
4. A method for making an amorphous silica-magnesia composite, comprising the steps of mixing a silicate solution and a magnesium sulfate solution.
5. 5. The method of claim 4, wherein the step of mixing the silicate solution and the magnesium sulfate solution is carried out such that the pH of the resulting mixture is in the range of 1 to 3.
6. The method according to claim 5, further comprising a step of performing an alkali treatment with aqueous ammonia after the step of mixing the silicate solution and the magnesium sulfate solution is performed so that the pH of the resulting mixture is in the range of 1 to 3.
7. 5. The method of claim 4, wherein the step of mixing the silicate solution and the magnesium sulfate solution is performed such that the pH of the resulting mixture is in the range of 9 to 11.
Citation Information
Patent Citations
Silica-magnesia composite oxide chromatographic filler
JP1994027097A
Silica-magnesia-based preparation excellent in base adsorptivity, and method for producing the same
JP2005006510A
Silica-magnesia formulation and method for producing the same
JP2005008675A
Treatment agent of waste water containing phosphate, and treatment method of waste water containing phosphate
JP2015178064A
Caffeine adsorbent and caffeine adsorption method
JP2018094512A